2022
DOI: 10.7717/peerj.13671
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level specialisation and interspecific resource partitioning in bees revealed by pollen DNA metabarcoding

Abstract: It is increasingly recognised that intraspecific variation in traits, such as morphology, behaviour, or diet is both ubiquitous and ecologically important. While many species of predators and herbivores are known to display high levels of between-individual diet variation, there is a lack of studies on pollinators. It is important to fill in this gap because individual-level specialisation of flower-visiting insects is expected to affect their efficiency as pollinators with consequences for plant reproduction.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…CO1 DNA barcoding has potential to improve the species identification of bees for field-based studies of foraging behaviour 30 , resource partitioning 31 and ecology 32 , but first requires that species assignment is not compromised by excessive intraspecific variation within the study location. Phylogenetic trees presented in the present study included sufficient reference barcodes of the 24 UK bumblebee species to provide context for both intra- and inter-specific variation of the CO1 locus in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…CO1 DNA barcoding has potential to improve the species identification of bees for field-based studies of foraging behaviour 30 , resource partitioning 31 and ecology 32 , but first requires that species assignment is not compromised by excessive intraspecific variation within the study location. Phylogenetic trees presented in the present study included sufficient reference barcodes of the 24 UK bumblebee species to provide context for both intra- and inter-specific variation of the CO1 locus in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that there is a larger degree in dietary variability than previously observed for O. cornifrons. Indeed,Klečka et al (2022) andGaiarsa et al (2022) demonstrated that generalist bee species in genus Ceratina are composed of many specialist individuals, and with more advanced DNA metabarcoding technology to track plant-pollinator interactions, future studies can glean more insight into individual variation within a species.…”
mentioning
confidence: 99%